Using conditioned suppression to investigate compulsive drug seeking in rats - Limpens, J.H.W.; Schut, E.H.S.; Voorn, P.; Vanderschuren, L.J.M.J. (Elsevier Ireland Ltd., 2014)
Background Persistent drug seeking despite harmful consequences is a defining characteristic of addiction. Recent preclinical studies have demonstrated the occurrence of this hallmark feature of addictive behaviour in rodents. For example, it has been shown that the ability of an aversive conditioned stimulus (CS) to suppress cocaine seeking was diminished after an extended self-administration history. The present study aimed to optimize the experimental conditions to examine conditioned suppression of sucrose and cocaine seeking in rats, and its dependence on the longevity of self-administration experience. Methods We investigated whether conditioned suppression depends on the intensity and quantity of footshocks during conditioning. In addition, the effects of CS omission, extinction and reconditioning were investigated, as well as the influence of the CS interval sequence on conditioned suppression. We also compared conditioned suppression after a limited and extended sucrose or cocaine self-administration history. Results We found that conditioned suppression depended on the intensity rather than the quantity of footshocks, whereby a higher footshock intensity was necessary to induce suppression of cocaine seeking compared to sucrose seeking. Conditioned suppression was most pronounced when the test started with presentation of the aversive CS, and conditioned suppression could be extinguished and reacquired. In addition, conditioned suppression of cocaine, but not sucrose seeking was reduced after extended self-administration experience. Conclusions These data provide a detailed analysis of conditioned suppression of cocaine and sucrose seeking. Importantly, we confirm the usefulness of conditioned suppression to study persistent drug seeking after prolonged drug self-administration.
Keywords: Cocaine; Sucrose; Self-administration; Conditioned suppression; Compulsive behaviour; Taverne